The Performance Multilevel Inverter 5 Level 1 Phase by Reducing Power Switch Components - Matalata, Hendi; Yandra, Fadli Eka (Jurusan Teknik Elektro Universitas Andalas, 2021)
Multilevel Inverter (MLI) is a converter that converts DC power source into AC power source with voltage output more than 2 levels. The conventional 5-level Multilevel Inverter Topology that is developing today generally uses eight power switch components. In this paper, research Topology multilevel inverter 5 levels was conducted by reducing the power switch components into four pieces and assisted by two diode clamps and capacitor as voltage coupling. PWM (Pulse Width Modulation) technique used to utilize multicarrier modulation. Simulation testing with MATLAB conducted has been verified with the results of hardware tests where the output voltage shows similarity of shape at the output voltage MLI 5 levels. The results and discussion of the proposed topology can provide economic benefits from the use of the number of power switch components (MOSFET) compared to conventional 5-level MLI topology.Keywords :Â Multilevel Inverter, PWM, 5 Level